New Insights Into Structure and Function of TIFY Genes in Zea mays and Solanum lycopersicum: A Genome-Wide Comprehensive Analysis - Heidari, Parviz; Faraji, Sahar; Ahmadizadeh, Mostafa; Ahmar, Sunny; Mora-Poblete, Freddy (Frontiers in Genetics, 2021)
The TIFY gene family, as a key plant-specific transcription factor (TF) family, is involved in diverse biological processes including plant defense and growth regulation. Despite TIFY proteins being reported in some plant species, to the best of our knowledge, a genome-wide comparative and comprehensive analysis of TIFY genes in plant species is lacking. In the current study, the members of the TIFY gene family are significantly enhanced by identification of 18 and 6 new members using maize and tomato reference genomes, respectively. Thus, a genome-wide comparative analysis of the TIFY gene family between 48 tomato (Solanum lycopersicum) genes as a dicot plant and 26 maize (Zea mays) genes as a monocot plant was performed in terms of sequence structure, evolutionary, expression, regulatory systems, and protein interaction. The identified TIFYs were clustered into four subfamilies including TIFY-S, JAZ, ZML, and PPD. The PPD subfamily was only detected in the studied dicots. Within the context of biological process, TIFY family genes in both studied plant species are predicted to be involved in various important processes such as reproduction, metabolic processes, response to stresses, and cell signaling. The Ka/Ks ratios of the duplicated paralogous gene pairs indicate that all the duplicated pairs in the TIFY gene family of tomato have been influenced by an intense purifying selection, whereas in the maize genome, there are three duplicated blocks containing Ka/Ks > 1, which are implicated in evolution with positive selection. The amino acid residues present in the pocket sites of TIFY proteins partially differ in each subfamily, although the Mg or Ca ions exist heterogeneously in the center of the active sites of all the predicted TIFY protein models. Based on the expression profile of TIFY genes in both plant species, we think that JAZ subfamily proteins are more involved in the response to adverse conditions compared with other subfamilies. In conclusion, by globally scrutinizing and comparison studying the maize and tomato TIFY genes, we too find that TIFY genes play a critical role in cell reproduction, plant growth, and dealing with stress conditions, and the conserved regulatory mechanisms may control their expression.